New Prostaglandins from the Soft Coral Sarcophyton ehrenbergi Marengeller of Andaman and Nicobar Islands of Indian Ocean - Sekhar, V. Chandra; Bheemasankara Rao, Ch.; Ramana, H.; Kuwar, M.M.K.; Venkata Rao, D. (Asian Journal of Chemistry, 2010)
New prostaglandins of PGB-type and hippurins have been isolated from the soft coral Sarcophyton ehrenbergi Marengeller, collected from the coasts of Andaman and Nicobar Islands of Indian Ocean along with a pregnane derivative, arachidonic acid and its ethyl ester. Their structures have been determined by spectral data.